Research Development on Cryopreservation Technique to Preserve Avian Semen - Tatan Kostaman; A.R. Setioko (Indonesian Center for Animal Research and Development, 2011)
Cryopreservation technique could be used to preserve animal cell, plant or other genetic materials (included semen) in frozen. In this case, the cryopreservation technique is a storage technique that carries out at very low temperature in liquid nitrogen at -196oC. At this temperature, semen does not experience the process of metabolism but still has the ability to live on when used later. Semen that is preserved by cryopreservation technique has unlimited shelf life. This method is more efficient in terms of cost, time, space, and labour than other methods. Cryopreservation techniques can be divided into conventional technique (controlled slow freezing) and rapid freezing technique. Besides cryopreservation of semen, other genetic material from avian that can be cryopreservesed is Primodial Germ Cells (PGC). Balitnak has succesfully isolated the PGC of some Indonesian native chickens. The success of cryopreservation is indicated by not only the high rate of survival, but also the fertility after cryopreservation. Key words: Avian, storage, cryopreservation, semen